2008
DOI: 10.1056/nejmoa0706585
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Blockade and Aortic-Root Dilation in Marfan's Syndrome

Abstract: ConclusionsIn a small cohort study, the use of ARB therapy in patients with Marfan's syndrome significantly slowed the rate of progressive aortic-root dilation. These findings require confirmation in a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
510
5
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 758 publications
(549 citation statements)
references
References 25 publications
10
510
5
16
Order By: Relevance
“…This is in contrast to the pathological role of TGF-␤ in the aortic aneurysms that form in MS, 6 as assessed by the efficacy of TGF-␤ blockade in both preventing aneurysms in the murine model of MS and slowing disease progression in patients with MS. 7 In marked contrast to the MS model, our data suggest that with an inflammatory stimulus, loss of elastin is prevented by induction of TGF-␤ and PAI-1-mediated repression of MMP-9 activation by plasmin. An unexpected observation is that TGF-␤ signaling is essential during this postnatal window of coronary artery development because TGF-␤ inhibition caused marked coronary wall thinning and dilation.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This is in contrast to the pathological role of TGF-␤ in the aortic aneurysms that form in MS, 6 as assessed by the efficacy of TGF-␤ blockade in both preventing aneurysms in the murine model of MS and slowing disease progression in patients with MS. 7 In marked contrast to the MS model, our data suggest that with an inflammatory stimulus, loss of elastin is prevented by induction of TGF-␤ and PAI-1-mediated repression of MMP-9 activation by plasmin. An unexpected observation is that TGF-␤ signaling is essential during this postnatal window of coronary artery development because TGF-␤ inhibition caused marked coronary wall thinning and dilation.…”
Section: Discussioncontrasting
confidence: 66%
“…In the murine model of MS, TGF-␤ blockade with either a neutralizing antibody (nAb) or the angiotensin-II receptor antagonist, losartan, effectively prevented aortic dilation and induced regression of established disease. 6 Furthermore, in a clinical study 7 in pediatric patients with MS, losartan therapy was effective in decreasing the rate of aortic root dilation. As a result of these studies, there has been speculation that increased TGF-␤ activation is related to non-MS aneurysm formation, leading to interest in extrapolating the use of TGF-␤ blockade to treat conditions such as abdominal aortic aneurysm and KD.…”
mentioning
confidence: 99%
“…In a mouse model of aortic dilation, treatment with losartan proved to be more effective than propranolol in reducing and reverting aortic wall disarray. 27 In agreement with this finding, two clinical trials recently demonstrated that the inhibition of the renin-angiotensin-aldosterone system by angiotensin-converting enzyme inhibitors 28 or angiotensin receptor blockers 29 reduced the rate of aortic enlargement in patients affected by Marfan's syndrome.…”
Section: Discussionmentioning
confidence: 62%
“…For patients with thoracic aortic aneurysm, it is reasonable to reduce blood pressure with beta blockers and angiotensin-converting enzyme inhibitors 103 or angiotensin receptor blockers 104,105 to the lowest point patients can tolerate without adverse effects. [100][101][102] (Level of Evidence: B) 2.…”
Section: Class Iiamentioning
confidence: 99%
“…An angiotensin receptor blocker (losartan) is reason able for patients with Marfan syndrome, to reduce the rate of aortic dilatation unless contraindicated. 105,112 (Level of Evidence: B)…”
Section: Class Iiamentioning
confidence: 99%